Effects of preslaughter stress and irradiation on physicochemical qualities of meat - Vivek A K (Department of Livestock Products Technology, College of Veterinary and Animal Sciences, 2006)
The effect of stress on the blood parameters and physicochemical qualities of meat as well as effect of irradiation on the qualities of fresh meat from stressed cattle were investigated in the present study. A total of 27 culled adult cattle from different farms were grouped into three, having nine animals in each group. Group I animals were considered as control while group II animals were transported for 2 h and slaughtered immediately after transport. Group III animals were transported for 6 to 7 h and given rest for 18 h before slaughter. Blood samples were collected prior to transport in all the animals, immediately after transport in group II and III and after 18 hours rest, before slaughter, in group III animals. Meat samples were collected from all the animals in which half of the samples were subjected to irradiation at 2.0kGy with gamma irradiation, as Cobalt 60 as source. The samples were stored at 40C for further studies. Animals in all the groups were having homogenous blood values prior to transport in cortisol, CK, BUN, creatinine and PCV. After transport, group II had a significant increase in cortisol (P<0.01), CK (P<0.01) and BUN (P<0.05), while group III had a significant increase in cortisol (P<0.01), CK(P<0.01), BUN (P<0.05) and creatinine (P<0.05) except PCV, in which the increase in cortisol and CK were significantly (P<0.01) greater than that in group II. By giving rest, even though there was significant (P<0.01) reduction in cortisol and CK values, the after rest values of cortisol (P<0.01), CK (P<0.01) and BUN (P<0.05) were significantly higher than that of the before transport values. In the case of pH and WHC, the trend was almost similar, with a higher value at zero hour and the decline was drastic in zero to 6 h, followed by 6 to 12 and 12 to 24 h and the control and irradiated samples did not show any significant difference in the decline. Cooking loss of the control and irradiated samples did not have a significant difference at zero hour storage, while the 24h storage brought a significant (P<0.01) increase in cooking loss in all the samples and irradiated samples had a significantly (P<0.05) higher cooking loss at 24h. Shear force values were significantly (P<0.01) less for irradiated samples while storage significantly (P<0.01) increased the values of all the samples. The Hunterlab colour values, L, a, b, C and hue angle, were significantly (P<0.01) higher in irradiated samples at zero hour storage. At 24h storage, the values were significantly (P<0.01) higher than that at zero hour, and only the hue angle values were significantly (P<0.05) higher in irradiated samples. Even though there existed a slight difference between control and irradiated samples in various organoleptic qualities like colour, flavour, juiciness and tenderness, there was no significant difference in overall acceptability between control and irradiated samples. In the present study, the differential response due to irradiation for the stress given to the animals, found to be statistically non significant leading to the result that irradiation conditions did not have an impact on the meat obtained from stressed animal.